Wtajemniczenie chrześcijańskie bramą i drogą do nowego życia paschalnego. Refleksja na kanwie propozycji bpa Zbigniewa Kiernikowskiego - Kiejkowski, Paweł (Poznańskie Studia Teologiczne, 2017)
Following the Second Vatican Council, the Catholic Church notices the need for the existence in particular dioceses of an institutional way of Christian initiation for adults who wish to follow the teachings of Jesus Christ. At the same time, there is a universal recognition of the need to organize in local churches and relatively big parishes special places where it would be possible for adults to gradually experience post-baptismal initiation. Zbigniew Kiernikowski, the Bishop of Legnica, offers us a comprehensive proposition of Christian initiation for adults, which can be experienced both prior to and after the celebration of the sacraments of Christian initiation. He updates the way of initiation in a very specific manner, which the Church recommends in the Rite of Christian initiation of adults adjusted to Polish customs. His proposition is firmly set in the biblical, liturgical, ecclesial and existential contexts. Its great asset is the author’s pastoral practice. The outline of the catechumenate and proposed catecheses were not created by him while sitting at a desk, but rather as a result of his ministry, the long-term programmes implemented personally in the dioceses of Siedlce and Legnica, the catecheses delivered, the scrutinies carried out and the sacraments celebrated. Yet, it needs to be stressed that the presented catecheses do not deal with all the essential dimensions of a Christian’s new life. Neither are they a systematic theological lecture on the sacraments of initiation. His numerous texts contain very interesting intuitions related to the existence of a new man, the Son of God, who is born thanks to being immersed in the waters of baptism. His proposition of experiencing initiation is incredibly valuable and unique against the backdrop of the Polish contemporary thought and sacramental practice.